Vocational High School Effectiveness Standard ISO 9001: 2008 for Achievement Content Standards, Standard Process and Competency Standards Graduates - Yeni Ratih Pratiwi (Jurnal Pendidikan Sains, 2013)
Efektivitas Sekolah Menengah Kejuruan Berstandar ISO 9001:2008 terhadap Pencapaian Standar Isi, Standar Proses dan Standar Kompetensi Lulusan Abstract: The purpose of this study was to determine differences in the effectiveness of the achievement of the content standards, process standards, and competency standards in vocational already standard ISO 9001: 2008 with CMS that has not been standardized ISO 9001: 2008 both in public schools and private schools. Data collection using the questionnaire enclosed Likert scale models. Analysis of data using one-way ANOVA using SPSS. The results showed: (1) there is no difference in effectiveness between public SMK ISO standard ISO standards with private SMK (P = 0.001); (2) there are differences in the effectiveness of public SMK SMK ISO standards with ISO standards have not (P = 0.000); (3) there are differences in the effectiveness of public SMK ISO standards with private vocational yet ISO standards (P = 0.000); (4) there are differences in the effectiveness of the private vocational school with vocational standard ISO standard ISO country has not (P = 0.015); (5) there are differences in the effectiveness of the private vocational bertandar ISO with private vocational yet standardized ISO (P = 0.000); (6) there was no difference in the effectiveness of public SMK has not been standardized by the ISO standard ISO private SMK yet. Key Words: vocational high school standards ISO 9001: 2008, the standard content, process standards, competency standards Abstrak: Tujuan penelitian ini untuk mengetahui perbedaan efektivitas pencapaian standar isi, standar proses, dan standar kompetensi lulusan pada SMK yang sudah berstandar ISO 9001:2008 dengan SMK yang belum berstandar ISO 9001:2008 baik pada sekolah negeri maupun sekolah swasta. Pengumpulan data menggunakan kuisioner tertutup model skala likert. Analisis data menggunakan ANOVA one way menggunakan program SPSS. Hasil penelitian menunjukkan: (1) ada perbedaan efektivitas antara SMK negeri berstandar ISO dengan SMK swasta berstandar ISO (P = 0,001); (2) ada perbedaan efektivitas SMK negeri berstandar ISO dengan SMK negeri belum berstandar ISO (P = 0,000); (3) ada perbedaan efektivitas SMK negeri berstandar ISO dengan SMK swasta belum ber-standar ISO (P = 0,000); (4) ada perbedaan efektivitas SMK swasta berstandar ISO dengan SMK ne-geri belum berstandar ISO (P = 0,015); (5) ada perbedaan efektivitas SMK swasta bertandar ISO de-ngan SMK swasta belum berstandar ISO (P = 0,000); (6) tidak ada perbedaan efektivitas SMK negeri belum berstandar ISO dengan SMK swasta belum berstandar ISO. Kata kunci: sekolah menengah kejuruan berstandar ISO 9001:2008, standar isi, standar proses, standar kompetensi lulusan